Amelia's itchy-twitchy, lovey-dovey summer at Camp Mosquito - Moss, Marissa (Simon & Schuster Books for Young Readers, 2008)
"Despite the hard mattresses, biting bugs, and exhausting hikes, Amelia finally begins to enjoy her time at sleepaway camp with the help of her new friends, but when she gets her first serious crush on a boy named Luke, Amelia is stunned to find out that Carly likes him too and so must find a way to win his heart without losing her newest best friend."--Publisher's information.